(untitled) (Al-Aasar, 2026)
This article examines Sarus Crane Have Flown Out of Their Dreams by Mazhar-ul-Islam through the lenses of time traveling, dreams, fantasy, and the aesthetics of super-realism. It argues that time travel in the novel is not governed by scientific mechanisms or technological logic, but unfolds as an inner, existential journey shaped by memory, love, dreams, and spiritual inheritance. Dreams function not merely as symbolic episodes but as active narrative forces that enable the crossing of temporal boundaries, while fantasy operates as an extension of reality rather than an escape from it. Central symbols such as the sarus crane, flight, the fallen feather, the tribe, and the antique store dismantle linear time and bring past, present, and future into a single experiential continuum. The study demonstrates that super-realism in this novel emerges from the fusion of dream, fantasy, and reality, revealing deeper truths of human consciousness and being. In this way, the novel stands as a distinctive example in Urdu fiction of creative freedom, literary time travel, and super-realist aesthetics